Fast and Simple Extraction for LCMSMS Analysis of Oxytetracycline Residue in Pork: https://doi.org/10.69692/SUJMRD1001107 - Chanthavong, Oudone; Sandkhamlue, Kengkham; Kongmany, Santi (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Pork is very popular as an animal-base protein source of peoples in the Lao PDR. The pig growth promotion, treatment and prevention of diseases frequently relies on the use of antibiotics. In terms of food safety, the analysis of antibiotic residue in pork would be therefore important. Oxytetracycline (OTC) is one of antibiotics used in the pig husbandry. In this study, a fast and simple extraction and analysis method for determining OTC residue in pork was developed. Briefly, 1.0 g of homogenized pork sample in a 50mL-centrifµge tube was extracted with 10 mL of CH3OH: H2O mixture (9:1 ratio) assisted with vortex for 10 min, treated with QuEChERS salt and subjected to centrifugation at 5000 rpm. The methanolic extract (1.5 mL) was then cleaned up with 2mL-dSPE tube (containing MgSO4, PSA, and C18), filtered through syringe filter 0.45 micron and analyzed with ESI-LCMS/MS optimized and operated in MRM positive mode. Calibration was prepared with OTC standard solutions (5-100 ng/g). The analytical method was validated with triplicated recovery tests at a spiked level of 50 ng/g. The results unveiled that the method gave very good recovery of 88.7±3.24%. The limits of detection (LOD) and quantification (LOQ) were achieved with 0.36 ± 0.02 and 1.19 ±0.04 ng/g. In consequence, the developed method would be suitable for OTC determination in pork samples.